Is it necessary to measure hepatic venous pressure gradient before liver resection in cirrhotic patients? A single center audit - Hassaan Bari; Sana Amir Akbar; Faisal Hanif (Journal of the Pakistan Medical Association, 2021)
Objective: To determine whether routine preoperative hepatic venous pressure gradient measurements are necessary in child’s-A cirrhotic patients undergoing liver resection for hepatocellular carcinoma, and to assess immediate post-operative liver dysfunction and 30-day mortality in such cases. Methods: The 3-year audit was done at Shuakat Khanum Memorial Cancer Hospital and Research Centre, Lahore, Pakistan, and comprised data from January 1, 2015, to December 31, 2017, of all Child’s class “A” patients with hepatocellular carcinoma without any clinical signs of portal hypertension who had preoperative hepatic venous pressure gradient measurements done were. A proforma was used to collect the required data from patient files. Data was analysed using SPSS 21. Results: Of the 20 patients, 11(55%) were males. The overall mean age was 60.6+7.4 years. Only 2(10%) patients had raised hepatic venous pressure gradient. Of the total, 14(70%) patients underwent surgery. Mean duration of surgery was 222+82.5 minutes and mean hospital stay was 6.8+3.2 days. None of the patients had deranged prothrombin-time or bilirubin on postoperative day 5. Conclusion: The incidence of subclinical portal hypertension was very low. Hepatic venous pressure gradient measurement can be avoided in early stage hepatocellular carcinoma for child’s A cirrhotic patients undergoing liver resection. Key Words: Portal hypertension, Hepatic venous pressure gradient, Continuous...